STUDENTLERDIŃ SÓYLEW ShEBERLIGIN RAWAJLANDÍRÍWDA INTERAKTIV ShÍNÍǴÍWLAR HÁM NOVERBAL KOMMUNIKACIYANÍŃ ROLI - Abatova, Mexriban Kuralbay qızı (SCIENCE and SOCIETY, 2026)
This article presents a scientific study aimed at developing students’ oratory skills. The study analyzes the impact of interactive classes, psychological training, and non-verbal communication methods. The article provides practical recommendations for enhancing students’ public speaking skills through methodological approaches.